THE IMPACTS OF THE BEAUTY MYTH ON THE EXISTENTIAL FREEDOM OF PECOLA IN TONI MORRISON’S THE BLUEST EYE - Asmarani, Ratna (Universitas Negeri Semarang, 2016)
The purpose of this paper is to analyse the destructive impacts of the beauty myth on the existential freedom of Pecola, the young, poor, black female character, in Toni Morrison‘s ―The Bluest Eye.‖ The analysis is done through feminist criticism supported by the concept of the beauty myth and beauty as well as Sartrean concept of existentialism. The result shows that the widely spread beauty myth blocks Pecola‘s existential freedom on the physical, consciousness, or social life level. All these lead to young Pecola‘s ruined existence.